Fusarium pseudograminearum biomass and toxin accumulation in wheat tissues with and without Fusarium crown rot symptoms - Xu, Fei; Shi, Ruijie; Liu, Lulu; Li, Shufang; Wang, Junmei; Han, Zihang; Liu, Wei; Wang, Hongqi; Liu, Jihong; Fan, Jieru; Wang, Aolin; Feng, Chaohong; et al. (Frontiers in Plant Science, 2024)
Fusarium crown rot (FCR) is an important and devastating disease of wheat (Triticum aestivum) caused by the fungus Fusarium pseudograminearum and related pathogens.Using two distinct susceptible cultivars, we investigated the isolation frequencies of F. pseudograminearum and quantified its biomass accumulation and the levels of the associated toxins deoxynivalenol (DON) and DON-3-glucoside (D3G) in inoculated field-grown wheat plants. We detected F. pseudograminearum in stem, peduncle, rachis, and husk tissues, but not in grains, whereas DON and D3G accumulated in stem, rachis, husk, and grain tissues. Disease severity was positively correlated with the frequency of pathogen isolation, F. pseudograminearum biomass, and mycotoxin levels. The amount of F. pseudograminearum biomass and mycotoxin contents in asymptomatic tissue of diseased plants were associated with the distance of the tissue from the diseased internode and the disease severity of the plant. Thus, apparently healthy tissue may harbor F. pseudograminearum and contain associated mycotoxins. This research helps clarify the relationship between F. pseudograminearum occurrence, F. pseudograminearum biomass, and mycotoxin accumulation in tissues of susceptible wheat cultivars with or without disease symptoms, providing information that can lead to more effective control measures.